2017
DOI: 10.5114/fmpcr.2017.65093
|View full text |Cite
|
Sign up to set email alerts
|

The influence of selected sociodemographic data on coping with stress by parents of hospitalized children

Abstract: Background. a child's illness is a major stress-inducing factor for parents. it alters interpersonal relationships in and outside the family unit and weakens the sense of safety. in stressful situations, everyone adopts certain behaviors that are defined as a stress-coping style. Objectives. the aim of the study was to analyze factors which contribute to the choice of a stress-coping style by parents of hospitalized children. Material and methods. this survey-based study was conducted among 292 parents of chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…individual factors are emphasized as stressful factors at work by others as well [4]. another study has revealed that younger age and female gender are significant predictors of a greater stress score [21][22][23]. What is more, lack of knowledge was seen as a factor influencing stress in yet a further study [26].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…individual factors are emphasized as stressful factors at work by others as well [4]. another study has revealed that younger age and female gender are significant predictors of a greater stress score [21][22][23]. What is more, lack of knowledge was seen as a factor influencing stress in yet a further study [26].…”
Section: Resultsmentioning
confidence: 99%
“…in addition, a straightforward pathway between work methods, including ergonomics, organizational systems, and work environments, has been identified. indeed, individuals with higher education score lower on the emotional exhaustion scale and more easily cope with stress [19,21]. another study has revealed that younger age, single status, and female gender are significant predictors of a greater stress score and/or more psychosocial needs [23].…”
mentioning
confidence: 96%
See 2 more Smart Citations